ANALISIS KELAYAKAN PENGEMBANGAN USAHA HOME INDUSTRY AZZCRAFT DI KABUPATEN PURWOREJO - , (Politeknik Sawunggalih Aji, 2020)
Home Industry AzzCraft is a business entity that operates in the home industry of clothing and souvenirs, namely souvenirs made from patchwork and knitted fabrics. This patchwork souvenir is a craft that utilizes household waste that is produced every day in sewing houses so that the waste becomes functional items. This research method uses quantitative and qualitative methods to find out whether the AzzCraft home industry business is feasible to develop as well as strategies for increasing sales turnover. Data collection techniques used in research include observation, interviews and documentation. And the data sources used are primary and secondary data. The results of this research show good results for legal aspects, market and marketing aspects, financial aspects, social economic aspects, and environmental impact aspects. The results of the analysis of financial aspects through the investment appraisal method are said to be quite feasible to carry out based on the results of the PBP (Pay Back Period) calculation of 1.675531592 - 1.67 months, namely 1 month 20 days. NPV (Net Present Value) = IDR 477,315.80 > 0. The IRR (Internal Rate of Return) value is 616% > the applicable interest value is 15%. The results of the BEP (Break Even Point) analysis in product units sold were 23 units and in rupiah sales were IDR 62,666